2022
DOI: 10.1016/j.jns.2022.120162
|View full text |Cite
|
Sign up to set email alerts
|

Mid and long-term neurological and neuropsychiatric manifestations of post-COVID-19 syndrome: A meta-analysis

Abstract: Importance: Neurological and neuropsychiatric symptoms that persist or develop three months after the onset of COVID-19 pose a significant threat to the global healthcare system. These symptoms are yet to be synthesized and quantified via meta-analysis. Objective: To determine the prevalence of neurological and neuropsychiatric symptoms reported 12 weeks (3 months) or more after acute COVID-19 onset in adults. Data sources: A systematic search of PubMed, EMBASE, Web of Science, Google Scholar and Scopus was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
418
13
43

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(505 citation statements)
references
References 54 publications
31
418
13
43
Order By: Relevance
“…A recent meta-analysis confirmed that fatigue, cognitive dysfunction and sleep disturbances are key features of post-COVID-19, but also highlighted that psychiatric manifestations such as sleep disturbances, anxiety, and depression increase significantly in prevalence over time [7]. Investigation of neuropsychiatric impacts and the pathophysiological drivers underlying the risk factors associated with COVID-19 are important in surveillance and in the development of evidence-based therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis confirmed that fatigue, cognitive dysfunction and sleep disturbances are key features of post-COVID-19, but also highlighted that psychiatric manifestations such as sleep disturbances, anxiety, and depression increase significantly in prevalence over time [7]. Investigation of neuropsychiatric impacts and the pathophysiological drivers underlying the risk factors associated with COVID-19 are important in surveillance and in the development of evidence-based therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms include fatigue, headache, cognitive compromise, dyspnea, and anosmia [5]. The association with higher number of symptoms [6] and the slow decrease of people having lasting symptoms [5, 7] suggests that the pathophysiological drivers underlying the presence of symptoms might be transient, such as inflammatory response. However, recent data shows that mild COVID-19 is related to important long-lasting symptoms, including neurological and psychiatric manifestations, and persistent sequelae, in about 30% of those patients, with increasing prevalence in aged individuals [8].…”
Section: Introductionmentioning
confidence: 99%
“…These were reported to have included cognitive dysfunction involving memory concentration, attention disorder, and in some cases sleep deprivation, which appeared to be the key features of post-COVID-19 syndrome. Normally, sleep deprivation and depression are the most common symptoms over time [ 99 , 100 , 101 , 102 ].…”
Section: Post Covid-19 Conditionsmentioning
confidence: 99%
“…According to the WHO, the most common symptoms include fatigue, shortness of breath, and cognitive dysfunction. Other common symptoms include depression, anxiety, headache, joint and muscle pain, sleep problems, and smell or taste disorders [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%